DigiDreams Digital Portfolio Development: Case Study of Creating a Web System for Restaurant Profiles and Traditional Food Menus Nusa Rasa - Gasendra, Hilda; Anjarwati, Tina (Ebiz Prima Nusa, 2024)
This internship report discusses the development of a digital portfolio conducted at DigiDreams with a case study of web system development for company profiles and traditional food menus at Nusa Rasa restaurant. The main objective of this internship is to assist in creating a portfolio of work that includes complete information about the restaurant profile and the traditional food menus offered. The process of developing this web system involves several stages, starting from needs analysis, design, implementation, to evaluation. Through a web-based information system development approach, the resulting portfolio is expected to increase DigiDreams' visibility as a provider of web, application, and other digital solution creation services. The results of this project show that the integration of web technology in presenting company profiles and food menus can improve restaurant operational efficiency and customer satisfaction. This internship provides practical experience in information system development and web design, as well as an in-depth understanding of the importance of digitalization in the traditional culinary industry. Thus, this report not only documents the process and results of the internship, but also provides insight into the application of information technology in supporting the sustainability of traditional restaurant businesses in the digital era.Keywords: Digital portfolio, Web system, Company profile, Food menu, DigiDreams, Nusa Rasa